(untitled) (Journal of Medical & Health Sciences Review, 2025)
The primary objective of this study was to formulate and evaluate Paracetamol Orally Disintegrating Tablets (ODTs) using different superdisintegrants and to assess their performance in varying dissolution mediums. The aim was to develop a robust ODT formulation with rapid disintegration, acceptable mechanical strength, and enhanced dissolution profile for pediatric and geriatric use. Five formulations (F1-F5) of Paracetamol ODTs (120 mg) were prepared by direct compression. The formulations varied in the type and concentration of superdisintegrants: Sodium Starch Glycolate (SSG) and Crospovidone (CP). Pre- compression parameters of the powder blends were evaluated. The tablets were assessed for weight variation, hardness, friability, drug content, wetting time, in- vitro disintegration time, and in-vitro drug release in two different mediums: simulated salivary fluid (pH 6.8) and phosphate buffer (pH 5.8). All formulations exhibited good pre-compression properties with angle of repose between 28.1°±0.6° and 32.5°±0.9°, indicating acceptable flow. Post-compression evaluation revealed that all tablets complied with pharmacopeial standards for weight variation (349.5±1.8 mg to 351.2±1.5 mg), hardness (3.2±0.3 to 4.1±0.2 kg/cm²), friability (<0.85%), and drug content (98.5±1.2% to 101.3±1.5%). Formulation F4, containing 8% w/w Crospovidone, showed the best overall performance with a remarkably low disintegration time of 18.4±2.1 seconds and a wetting time of 25.6±3.2 seconds. Dissolution studies indicated that F4 achieved 99.2±1.8% drug release in pH 6.8 and 97.5±2.1% in pH 5.8 within 10 minutes, which was significantly higher than other formulations. The study successfully developed Paracetamol ODTs with superior disintegration and dissolution characteristics. Crospovidone at 8% w/w concentration was found to be the most effective superdisintegrant. The dissolution medium pH had a slight but statistically significant effect on the drug release rate, with faster release observed in simulated salivary fluid (pH 6.8). Formulation F4 is identified as the optimal formulation for rapid onseta of action and improved patient compliance.